Synergy of novel coumarin derivatives and tamoxifen in blocking growth and inducing apoptosis of breast cancer cells - Ballazhi, Lulzime; Imeri, Faik; Dimovski, Aleksandar; Jashari, Ahmed; Popovski, Emil; Breznica-Selmani, Pranvera; Mikhova, Bozhana; Dräger, Gerald; Alili-Idrizi, Edita; Mladenovska, Kristina (Macedonian Pharmaceutical Association, 2014)
Possible synergistic effect of tamoxifen (2 μM) and hydrazinyldiene-chroman-2,4-diones (10-100 μM) was examined with an aim to create more effective treatment for ER+ breast cancer. Anti-breast cancer effect has been evaluated on the proliferation of MCF-7 breast adenocarcinoma cells using MTT and alamarBlue assays. Cell viability was evaluated after 48h-treatment and the ICs50 of the coumarin derivatives were determined. The apoptotic effect was evaluated by detection of PARP cleavage and reduced activity of the survival kinase Akt. The results demonstrated dose-dependent activity, with a percent of growth inhibition after combination treatment being significantly higher (53% to 79%, 10 μM and 100 μM, respectively) than the one in the cell lines treated with tamoxifen (29% to 37%) and the synthesized coumarin derivatives alone (11% to 68%, 10 μM and 100 μM, respectively). The ICs50 of the synthesized compounds significantly decreased in synergy with tamoxifen (33% to 51%). Coumarin derivative having thiazole moiety with additional methyl groups attached to the carbons at positions 5 and 4 in the thiazole ring showed to be the most potent, with IC50 20 µM when administered alone and 10 µM in synergy with tamoxifen. The levels of phospho-Thr308 Akt were down-regulated by the combination treatment, pointing to tyrosine kinase phosphorylation inhibition. In conclusion, the novel coumarin derivatives enhance the activity of tamoxifen and this combination may be suitable for prevention of ER+ breast cancer or development of related compounds. Further studies are needed to elucidate precisely the type of receptor involved in the activity and the mechanism of action.